2006
DOI: 10.1186/cc4962
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction Correct bedside measurement of intra-abdominal pressure (IAP) is important. The bladder method is considered as the gold standard for indirect IAP measurement, but the instillation volumes reported in the literature vary substantially. The aim of this study was to evaluate the effect of instillation volume on intra-bladder pressure (IBP) as an estimation for IAP in critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…With respect to the effect of instillation volume on intra-bladder pressure as an estimation of IAP, large volumes of saline, as much as 100 to 250 ml, may lead to the overestimation of IAP (Malbrain and Deeren, 2006;Vallee et al, 2010), while a minimal volume as low as 2 to 10 ml is sufficient for the IAP signal transduction de Laet et al, 2008b). In terms of zero reference points for IAP measurement, various levels have been suggested such as the symphysis pubis, the phlebostatic axis, and the midaxillary line, each of which may result in different IAP measurements within the same patient.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the effect of instillation volume on intra-bladder pressure as an estimation of IAP, large volumes of saline, as much as 100 to 250 ml, may lead to the overestimation of IAP (Malbrain and Deeren, 2006;Vallee et al, 2010), while a minimal volume as low as 2 to 10 ml is sufficient for the IAP signal transduction de Laet et al, 2008b). In terms of zero reference points for IAP measurement, various levels have been suggested such as the symphysis pubis, the phlebostatic axis, and the midaxillary line, each of which may result in different IAP measurements within the same patient.…”
Section: Discussionmentioning
confidence: 99%
“…(8,10,13,16,18,25,26) A prospective study involving 13 intensive care unit (ICUs) in Belgium, Austria, Israel, Brazil and Australia reported IAH and ACS prevalence of 32.1% and 4.2%, respectively, upon patient admission. (5,16) A second study revealed significantly higher mortality indices in critically ill patients presenting with increased IAP compared to unaffected patients (37.9% and 19.1% respectively).…”
Section: Discussionmentioning
confidence: 99%
“…(16,26,27) Clinical presentation generally includes a tense, distended abdomen, hypotension, high airway pressure, hypercapnia and oliguria. (25) …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations